2010
DOI: 10.1017/s0272263110000045
|View full text |Cite
|
Sign up to set email alerts
|

Learning Without Awareness Revisited

Abstract: The role of awareness or consciousness in learning has been a relatively contentious issue in non-SLA fields (e.g., cognitive psychology). With the publications of Williams (2004, 2005), a similar debate appears to be brewing in the field of SLA. Contrary to Leow (2000), who reported that unawareness did not appear to play an important role in second or foreign language development, Williams (2005) offered empirical evidence that learning without awareness appears to be feasible. At the same time, it is also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(163 citation statements)
references
References 38 publications
7
153
3
Order By: Relevance
“…This result suggests that adults can make form-meaning connections in the absence of awareness. However, this finding has been difficult to replicate (Hama & Leow, 2010; Stutenberg & Morgan-Short, 2011), suggesting that implicit second language learning may occur at only a weak level and/or that there may be considerable variability in this ability among different participants. Nonetheless, later studies have found additional evidence for implicit second language learning in adults using reaction-time methodology, which may be more sensitive to implicit learning than a forced-choice decision task.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that adults can make form-meaning connections in the absence of awareness. However, this finding has been difficult to replicate (Hama & Leow, 2010; Stutenberg & Morgan-Short, 2011), suggesting that implicit second language learning may occur at only a weak level and/or that there may be considerable variability in this ability among different participants. Nonetheless, later studies have found additional evidence for implicit second language learning in adults using reaction-time methodology, which may be more sensitive to implicit learning than a forced-choice decision task.…”
Section: Discussionmentioning
confidence: 99%
“…Other subjects seem to remain completely unaware of the conditioning factor but still exhibited a small but statistically significant animacy bias in their responses. Even though it cannot be conclusively claimed that these subjects had no awareness whatsoever at the point of learning, and although both an earlier experiment by Williams (2004) and a recent replication study by Hama and Leow (2010) failed to find evidence of learning without awareness, Williams' findings are interesting and intriguing, suggesting that "implicit learning of form-meaning connections is possible, at least in principle" (2004, p. 298). Williams' finding that implicit learning in these experiments was correlated with participants' prior knowledge of languages with grammatical gender is equally intriguing, suggesting that prior experience in language learning may play a role in implicit learning.…”
Section: Major Challenges and Objections To The Noticing Hypothesismentioning
confidence: 98%
“…In the SLA literature, driven by the wellknown acquisition-learning distinction made by Krashen (1981Krashen ( ,1985Krashen ( , 1994Krashen ( , 2003, the possibility of SLA without awareness has been disputed (DeKeyser, 2003;Dornyei, 2009;Ellis, 1994Ellis, , 2007Hulstijn & Schmidt, 1994;Robinson, 1995aRobinson, , 2003Robinson, , 2007Robinson et al, 2011;Schmidt, 1995b;Williams, 2009) and empirically examined (N. DeKeyser, 1995;Hama & Leow, 2010;Hulstijn & DeKeyser, 1997;Hulstijn & R. Ellis, 2005;Robinson 1996Robinson , 1997bRosa & Leow, 2004;Williams, 2005Williams, , 2010, to name just a few).…”
Section: Implicit and Explicit Learning In The Context Of Fla Vs Slamentioning
confidence: 99%
“…When the thinkaloud protocol itself produces learning effects, this is called positive reactivity while when it interferes with ongoing learning processes, this is called negative reactivity. In the implicit SLA literature, some studies employed the thinkaloud protocol as an alternative measure of awareness to the verbal report (Hama & Leow 2010;Rosa & O'Neill 1999;Rosa & Leow 2004). O'Neill (1999, see also Rosa & investigated the roles of explicit grammar explanation and explicit instruction to search for rules underlying training stimuli in learning Spanish contrary-to-the fact conditionals in the past.…”
Section: The Issue Of Reactivity In Online Think-aloud Protocolmentioning
confidence: 99%
See 1 more Smart Citation